Study of cytological changes in normal appearing oral mucosa of smokers - Faisal, Ghasak Ghazi (2013)
Objective: To investigate the cytopathological effects of smoking in normal appearing oral mucosa of smokers namely, inflammation, hyperkeratinisation and dysplasia and to compare with the cytological smear of non-smokers. Materials and methods: Oral smears were obtained from the side of the tongue and floor of the mouth of 40 smokers with normal oral mucosa and 40 non-smokers were used as controls. Two samples have been collected from each patient by Cytobrush. The smears were histochemically stained by Papanicolaou stain and examined under light microscope for the mentioned cytological changes. Results: The smokers group showed 63% inflammation, 26% mild dysplasia and 36% hyperkeratinisation. The control group showed 35% inflammation, 2% mild dysplasia and 12% hyperkeratinisation. There was a statistically significant difference in the presence of inflammation, hyperkeratinisation and dysplasia (P<0.005) between the smokers and non-smokers groups. Conclusion: Brush biopsy screening can be used in clinic as adjunct in the early diagnosis of premalignant changes that can help prevent the occurrence of oral squamous cell carcinoma. The procedure is fast, painless and inexpensive.